Trace doping by fluoride and sulfur to enhance adsorption capacity of manganese oxides for lithium recovery - Fangren Qian; Bing Zhao; Min Guo; Zhiqiang Qian; Zhijian Wu; Zhong Liu (Materials & Design, 2020)
The H1.6Mn1.6O4 (HMO) derived from Li1.6Mn1.6O4 (LMO) has been aroused enormously attention due to high adsorption capacity. Through surface trace doping of F and S (LMO-R, R = F, S), the cycling stabilities and adsorption abilities of Li1.6Mn1.6O4 are improved. The adsorption uptakes are increased from 26.1 mg/g (before doping) to 33.4 and 27.9 mg/g at Li+ concentration of 12 mmol/L, respectively. In addition, first-principles calculations further confirm that F and S substitutes for O at 32e sites, leading to an improvement of the Li+ uptake rate. The Li+ adsorption capacities in the cycling process are enhanced by F and S doped, which may result from improving the charge density and offering more charge carriers that can participate in the ad/desorption reaction. The effect of the F and S substitution on adsorption capacity is discussed.